Analysis Of Container Yard Capacity in TPK Semarang - Arif, An Zaenal; Suwandi, Putri Anggi Permata; Kristiawan, Agung (Science and Technology Research Centre, Universitas PGRI Semarang, 2024)
TPK Semarang is one of the container terminals located in the Tanjung Emas Port area, Semarang which has a special pier or terminal for container ship activities, where the Semarang Container Terminal area is in the Tanjung Emas Port area, Semarang in Central Java Province. It should be noted that the Yard Occupancy Ratio (YOR) in 2022 is 46%, based on the UNCTAD standard YOR classification, which is sufficient, given the condition of the existing stockpiling yard area. Semarang TPK is still able to serve the growing flow of containers until 2032, this is related to the yard occupancy ratio (YOR). In the 2032 analysis, the YOR value at TPK Semarang reached 79% and was included in the high category so that it would affect the level of service at the terminal.